Prototipe Sistem Elektronis Berbantuan PC untuk Pemantauan Kondisi Pasokan Daya Listrik - Arief Goeritno; Yudha Herutama (Universitas Syiah Kuala, 2018)
The prototype of the electronic system aided personal computer for monitoring the condition of the electric power supply have been done. The principle for fabricating the prototype of the electronic system based on the mechanism of handshaking system between electronic systems and line port for a printer. Program embedded on a personal computer with certain specifications for the operation of the system. The prototype of the electronic system consists of 3 (three) main subsystems, namely the diver circuit, sensor circuit, and the circuit of electrical installations analogy. Measuring against the prototype performance is carried out on the port line for the printer, driver circuit, sensor circuit, and electrical installation analogy circuit. The path performance on the port line for the printer is focused on high or low logic on each port. Data port condition is used to process data transmission, while the status and control port conditions are used to process data reception. The performance of the control circuit is very much determined by inputting data from the user so that it is closely related to the data port. The performance of the sensor circuit is very much determined by the condition of the electrical installation analogy, so it is closely related to the status and control ports. The performance of the circuit of electrical installation analogy is marked by the presence of a voltage value, and if the voltage measured in the electrical installation is 220 volts AC, then it is as an installation marker inactive condition. Overall the system is capable of 8 remote monitoring points so that the condition of the electrical power supply through the electrical panel can be monitored at any time.